2002
DOI: 10.1021/ja012105n
|View full text |Cite
|
Sign up to set email alerts
|

Abrupt Interfacial Transitions of Hydrophobic Polysilanes As Probed via Liquid Crystal-Assisted Stepwise Deposition

Abstract: The Langmuir-Blodgett deposition was applied for the first time for fully hydrophobic polysilanes, poly(di-n-hexylsilane) (PDHS) and poly(methyl-n-octylsilane) (PMOS). The monolayer formation of such hydrophobic polysilanes was achieved by cospreading with a liquid crystal molecule, 4'-pentyl-4-cyanobiphenyl (5CB). The UV-visible absorption spectra showed that the backbone conformations of the polysilanes are completely different from that in the bulk. The layer-by-layer deposition allowed for the nanometer le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Layer-bylayer transfer of the monolayer onto a substrate further leads to valuable information on the conformational behavior of the polymer. 57 Although this knowledge gives new implications in polymer nano-processing, details are not described here because this topic is somewhat deviated from the framework of this article.…”
Section: Photocontrol Of Two Dimensional Phase Separationmentioning
confidence: 99%
“…Layer-bylayer transfer of the monolayer onto a substrate further leads to valuable information on the conformational behavior of the polymer. 57 Although this knowledge gives new implications in polymer nano-processing, details are not described here because this topic is somewhat deviated from the framework of this article.…”
Section: Photocontrol Of Two Dimensional Phase Separationmentioning
confidence: 99%
“…Moreover, molecular integration at the interface occasionally gives characteristic molecular assemblies that are different from those formed in the bulk states due to the 2D confinement effects. [45][46][47][48][49] Recently, we reported monolayer behaviour of bolaamphiphile 1 with a biphenyl core and flexible trisiloxane spacers (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…Because of this unique property, the application of polysilane for ordered materials in the nanometer scale is an interesting theme both scientifically and technologically [15][16][17]. In our previous study, we found that radiation-modified polysilane forms nanoscale micelles in selective solvents [18,19].…”
Section: Introductionmentioning
confidence: 94%